Przejawy kultury konsumpcyjnej w zachowaniach edukacyjnych młodzieży akademickiej. Opinie studentów o ściąganiu i plagiacie na podstawie badań empirycznych = Manifestations of consumption culture in the educational behariour of the academic youth. Students` opinions about cheating and pagiarism on the basis of empirical studies - Uklańska, Katarzyna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article discusses academic youth`s attitude towards cheating and plagiarism. The authors present the results of empirical studies conducted in 2015 among students of Cardinal Stefan Wyszyński University (Uniwersystet im. Kardynała Stefana Wyszyńskiego) in Warsaw. Consumption culture, stimulating this type of behavior, is the theoretical background for the analysis. However, such a theoretical perspective does not mean that the propensity for cheating and plagiarism has appeared in Polish conditions at the beginning of the 1990s (and the development of consumption culture).
Keywords: młodzież; studenci; plagiat; postawa; youth; students; fundaments; plagiarism